2009
DOI: 10.1160/th09-04-0250
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and immunoregulatory effector mechanisms in human endothelial cells

Abstract: In infectious diseases, interferon-gamma (IFN-gamma) is generally accepted as one of the most important inducers of antimicrobial and immunoregulatory effects, and both seemingly contradictory effects, can be mediated by the same effector molecules. In detail, several IFN-gamma induced enzymes such as the inducible nitric oxide synthase (iNOS) as well as the indoleamine 2,3-dioxygenase (IDO) also exert this double function. In this review we focus on antimicrobial and immunoregulatory properties of both enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 64 publications
0
18
1
Order By: Relevance
“…Previous studies have also found expression of IDO in endothelial cells (ECs) (28, 29). We similarly found that CD31 + ECs in lesional skin colocalized with both IDO and KYNU (Figure 2G).…”
Section: Resultsmentioning
confidence: 93%
“…Previous studies have also found expression of IDO in endothelial cells (ECs) (28, 29). We similarly found that CD31 + ECs in lesional skin colocalized with both IDO and KYNU (Figure 2G).…”
Section: Resultsmentioning
confidence: 93%
“…In many though not all situations, addition of exogenous l -Trp attenuates growth inhibition, consistent with the notion that limitation of this essential amino acid by IDO1 at least in part explains the antimicrobial activity observed. The antimicrobial activity of IDO1 in human endothelial cells has been reviewed recently (81). …”
Section: Role Of Trp Degradationmentioning
confidence: 99%
“…In situations where pro-inflammatory stimuli act on and induce MHC-II expression in placental endothelial cells, the ensuing immune response may, however, be modulated by endothelial IDO1. An antibacterial and antiparasitic role of endothelial IDO1 may be anticipated, and this might contribute to protection of the feto-placental unit against infection (81). …”
Section: Role Of Trp Degradationmentioning
confidence: 99%
“…2 IDO has immunologic functions. In the initial stage of some infectious diseases it can, by depleting TRP, inhibit the growth of the pathogens 3 and thereby disease progression. In the later stages, IDO may be involved in regulating immune responses and creating immune tolerance, acting as a protective feedback mechanism against an overzealous T-cell response.…”
mentioning
confidence: 99%
“…A number of hyperglycemia- and dyslipidemia-activated pathways leading to retinal endothelial cell and neural cell dysfunction have been identified. 321 Thus, the loss of neurons is also observed as part of the pathophysiology 2229 ; ultimately the summation of these aberrant events can lead to vision loss and even blindness.…”
mentioning
confidence: 99%